Efektivitas Penegakan Hukum oleh Kepolisan terhadap Pelaku Tindak Pidana Pencurian Kendaraan Motor (Curanmor) di Wilayah Polsek Kota Timur Kota Gorontalo - Junaedy Arter Andasia; Bunga, Marten; Robby Waluyo Amu (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study aims to analyze the effectiveness of law enforcement by the police against perpetrators of motor vehicle theft in the jurisdiction of Kota Timur Police Sector, Gorontalo City, and to identify the factors that influence its implementation. This research applies empirical legal research with a field-based approach. Data were obtained through interviews with investigators at Kota Timur Police Sector and through an examination of motor vehicle theft case data from 2022 to 2025. The results show that law enforcement against motor vehicle theft has been carried out through several stages, including receiving police reports, conducting inquiries and investigations, arresting suspects, preparing case files, and transferring cases to the public prosecutor. The case data indicate that all recorded cases during the research period were resolved. However, the effectiveness of law enforcement has not been fully optimal due to fluctuations in the number of cases and the possibility of repeat offenses. Several factors influence the effectiveness of law enforcement, including legal substance, law enforcement officers, facilities and infrastructure, community participation, and legal culture. The main obstacles include the limited number of investigators, heavy workloads, inadequate supporting facilities, and low public participation in providing information. Therefore, strengthening the capacity of police officers, improving investigative facilities, increasing routine patrols, and enhancing public legal awareness are necessary to improve the effectiveness of law enforcement against motor vehicle theft.